Effects of different levels of cave bats guano on chilli plant growth - Siti-Syamim Nurfatihah, Abd Rahman; Mohamad Fhaizal, Mohamad Bukhori (Malaysian Society for Molecular Biology and Biotechnology, 2025)
Chilli plants (Capsicum annuum) from the Solanaceae family are among the most widely cultivated crops globally. However, chilli plants are susceptible to numerous threat that can limit production, including pests, diseases, and environmental stressors that cause flower and fruit drop. Fertilization is critical for optimizing chilli yields, with studies showing that the application of fertilisers can substantially improve plant growth and yield. Bat guano, a highly nutrient-dense organic fertiliser rich in nitrogen, phosphorus, potassium, carbon, and beneficial microbes, has been used for centuries to improve crop growth in various countries. The present study investigates the effects of cave bat guano on several growth parameters in chilli plants, including plant height, leaf count, flower production, and fruit yield. For this study, guano was collected from Wind Cave Nature Reserve and Raya Cave in Sarawak. The experiment involved treating 81 chilli plants with three different guano levels (2.5 g, 5.0 g, and 7.5 g), along with a control group that received no treatment. Plant height, leaf count, and counts of flower buds, flowers, and fruits were measured monthly. Bat guano, especially at a rate of 7.5g per plant, was found to substantially improve chilli plant growth, flowering, and fruiting. The control group, by contrast, exhibited stunted growth, underscoring the importance of nutrient supplementation in achieving optimal growth. These findings are in line with prior research on guano applications, establishing it as a valuable organic fertiliser with the potential to boost agricultural productivity in Malaysia.